THE EFFECT OF EDUCATION LEVEL, EMPLOYEE PERFORMANCE, AND PERSONAL TECHNIQUES ON THE EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEM UTILIZATION(A Study on Village Credit Institutions in Tabanan District) - Ni Kadek Ayu Mita Suandewi Putri; I Ketut Yadnyana (CV. Adiba Aisha Amira, 2025)
The Accounting Information System (AIS) serves as an essential instrument for converting transactional data into financial information that supports decision-making processes. The effectiveness of an AIS reflects the extent to which an organization is capable of managing data efficiently and achieving its objectives. Village Credit Institutions (LPDs) in the Tabanan District have shown notable progress in financial management; however, they continue to encounter challenges such as limited training opportunities and recurring errors in data entry. This study aims to examine the effect of education level, employee performance, and personal techniques on the effectiveness of AIS usage. A quantitative approach was employed, involving a total sample of 65 respondents across 13 LPDs using a saturated sampling technique. The data analysis techniques used include validity tests, reliability tests, multiple linear regression analysis, F-test, and t-test. The findings reveal that education level has a positive and significant effect on the effectiveness of AIS utilization, employee performance also has a positive and significant effect, and personal techniques likewise exert a positive and significant influence on the effectiveness of AIS utilization.